2020
DOI: 10.1007/s13595-020-00959-9
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing stand density favors resistance, resilience, and recovery of Quercus petraea trees to a severe drought, particularly on dry sites

Abstract: & Key message Decreasing stand density increases resistance, resilience, and recovery of Quercus petraea trees to severe drought (2003), particularly on dry sites, and the effect was independent of tree social status. & Context Controlling competition is an advocated strategy to modulate the response of trees to predicted changes in climate. & Aims We investigated the effects of stand density (low, medium, high; relative density index 0.20, 0.53, 1.04), social status (dominant, codominant, suppressed), and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Tree size, species, competition, and magnitude and duration of drought influence resistance, recovery, and resilience of stands to drought (Sohn et al, 2016;Schmitt et al, 2020;Steckel et al, FIGURE 7 | Effects of tree size (A,C) and aspen basal area (B,D) on white spruce resistance (Rt) and resilience (Rs) in 2013. Aw_baha = aspen basal area (m 2 ha −1 ) and ba_b = initial tree size (m 2 ).…”
Section: Does Thinning Influence Resistance Recovery and Resilience Of These Stands To Drought?mentioning
confidence: 99%
“…Tree size, species, competition, and magnitude and duration of drought influence resistance, recovery, and resilience of stands to drought (Sohn et al, 2016;Schmitt et al, 2020;Steckel et al, FIGURE 7 | Effects of tree size (A,C) and aspen basal area (B,D) on white spruce resistance (Rt) and resilience (Rs) in 2013. Aw_baha = aspen basal area (m 2 ha −1 ) and ba_b = initial tree size (m 2 ).…”
Section: Does Thinning Influence Resistance Recovery and Resilience Of These Stands To Drought?mentioning
confidence: 99%
“…After-stress effects are more uncertain, and published results are heterogeneous and somewhat contradictory (see meta-analyses in Sohn et al, 2016 andCastagneri et al, 2021). Resilience increased in general after thinning (Sohn et al, 2016;Navarro-Cerillo et al, 2019;Schmitt et al, 2020;Lucas-Borja et al, 2021), although Castagneri (2021) did not found consistent results. A higher heterogeneity is reported for growth recovery.…”
Section: Thinning Decreased Drought Vulnerabilitymentioning
confidence: 99%
“…Q. petraea stands in Czech Republic responded well to thinning with a clear effect on diameter increment, less on height increment (Fedorová et al 2016). Thinning has been shown to reduce adverse effects of droughts and increases drought resistance of Q. petraea in France (Breda et al 1995, Schmitt et al 2020). Survival of sessile oak growing in Hungary was found to be moderately increased after thinning, with even stronger positive effects for coexisting Carpinus betulus L., the European hornbeam (Tinya et al 2020).…”
Section: )mentioning
confidence: 99%